2016
DOI: 10.1371/journal.pone.0166141
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Antibiotics to Prevent Acute Endophthalmitis after Ophthalmic Surgery: A Systematic Review and Meta-Analysis

Abstract: BackgroundPost-operative endophthalmitis is a rare and dreaded complication in ophthalmic operations because it often induces irreparable vision loss. Although many ophthalmological studies aimed at reducing the rate of endophthalmitis have been performed around the world, controversy continues to surround some issues, including the choice of antimicrobials and their route of administration, duration and timing. The aim of this study is to investigate some of these unresolved issues.MethodsA systematic review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…Other reviews and meta-analyses on this topic leave the question as to the added value of this study. 6970 Given that ECCE is known to have increased POE rates, 71 this study aims to represent the most current practice methods with only phacoemulsification cases. Additionally, this study compared IC alone to IC plus topical postoperative antibiotics to assess the impact on POE incidence.…”
Section: Discussionmentioning
confidence: 99%
“…Other reviews and meta-analyses on this topic leave the question as to the added value of this study. 6970 Given that ECCE is known to have increased POE rates, 71 this study aims to represent the most current practice methods with only phacoemulsification cases. Additionally, this study compared IC alone to IC plus topical postoperative antibiotics to assess the impact on POE incidence.…”
Section: Discussionmentioning
confidence: 99%
“…[ 34 ] The question of preferred practice for prevention of endophthalmitis has been studied time and again by several investigators and societies. [ 6 22 24 35 36 37 38 ] The use of preoperative and perioperative antibiotics varies widely between and within countries. Unavailability of Aprokam outside the European region explains why the 2014 ASCRS survey found that, in addition to cefuroxime, vancomycin and moxifloxacin are also commonly used by those respondents injecting antibiotics intracamerally.…”
Section: Intracameral Antibiotics During Cataract Surgerymentioning
confidence: 99%
“…I 2 statistics will be used to assess heterogeneity among studies. We consider the value of I 2 from 0% to 24%, 25%–50% and greater than 50% as low, moderate and high heterogeneity 29. Meta-regression model will be used to explore reasons, if heterogeneity is moderate and high.…”
Section: Methodsmentioning
confidence: 99%